ANTIRECESSIONARY ORGANIZATIONAL-ECONOMIC APPROACHES TO THE MODERN SCIENCE INTENSIVE DEFENSE ARTICLES PRICE FORMATION - V. Y. Ivanisov (Real Economics Publishing House, 2014)
The crisis of the enterprises that develop science intensive defense articles is caused by the loss of the research-and-production potential of these enterprises during the reformation of the Russian economy. The state customer that applies economic-organizing approaches, which don’t correspond to the development, now complicates restoration of the research-and-production potential science intensive defense articles developers. State customer economic-organizing approaches to the development are applied using contract development management system on the formation of the price and volume of the state contract development funding. The contract development management system in price formation (and funding alike) of the development doesn’t correspond the development as an object of management. Such inconsistency is one of the main reasons of cur-rent crisis of the science intensive product developers. First of all, the crisis of the science intensive product developers shows in the drop of the quality and low profitability of the science intensive defense articles. The article proposes the antirecessionary economic-organizing approaches to the price formation of the defense articles development that correspond to the peculiarities of the development, provide the state support of the defense articles developers’ research-and-production potential recovery, provide the antirecessionary development management and should be used in contract development management system